Geografia agrária e modernidade na Amazônia brasileira : "terras esplêndidas, que poderiam dar a todos o que a quase todos negam" - Ribeiro, Alyson Fernando Alves (2020)
Commodity is the phenomenal genesis of capital. The dynamics of capital is to subjugate everything to the process of commodification. The main objective of this thesis is to analyze land-commodity as a phenomenon of reiterating the permanence of modernity and the process of primitive accumulation of capital in the Brazilian Amazon. Therefore, the choice of the Amazon as the “frontier” of accumulation does not escape the principles that the capitalist system conceives of it. The hypothesis listed in this thesis is based on the argument of the persistence of the philosophical parameter of modernity through a geographical materiality in which the (re) production of land-commodity in the Legal Amazon, by the process of primitive accumulation, is the founding condition-way-product of the capital-space relationship, within the historical negation of Agrarian Reform. The present study conceived of dialectical historical materialism as a structuring method, which obliges us to consider space as a part of the whole; a historical product, a projection of society through the relations of production that emanate from unequal and combined contradictions of capitalism. This view allowed us to admit that through the various invasion phases, the Amazon offers its natural resources, mainly land and water, to satisfy the needs of the world market. The present analysis was developed through the following research tools: bibliographical search, statistical research in institutions and organizations, participation in meetings of entities that represent the struggle for land, data collection, preparation of graphs, charts, tables and cartograms, and fieldwork with questionnaires and semi-structured interviews. In the current framework of the capitalist relations, the Amazon presents itself as a response-resource for accumulation crises. It is a territory that has always been explored-consumed by what was most "new" in each historical moment, in a process of symbiosis between the archaic and the modern, stemming from the tragic bourgeois conception of linear progress as a derisory course: National Integration Plan (PIN); Amazon Agricultural and Agrimining Centre Program (POLAMAZÔNIA); National Development Plans (PND I, PNDII); Program of Land Redistribution and Stimulation to the North and Northeast Agroindustry (PROTERRA); Colonization. On May 12, 2017, the presidency of Michel Temer sanctioned Law 13.465/2017, in Brasilia, which eases the land regularization of the Union, under the name of the National Land Regularization Program. The referred legal reorganization, constitutive of the agribusiness territorial agenda, has as main innovation, the enlargement of the regularization area in Union lands, which goes from 1,500 to 2,500 hectares, throughout the national territory, which includes the increase of possessions to be legalized by the Land Legal Program in the Amazon. This “new land law in Brazil” represents a territorial agenda for agrihydrobusiness. As a reflection of this panorama, the geography of agrarian conflicts in the Brazilian Amazon has grown (re) producing conflicts for land and territory. Barbarism as a manifestation of violence appears as a systemic structure of capitalism, it is a living present, those who believe it is past are mistaken. The indigenous land of the Uru-Eu-Wau-Wau ethnic group is being invaded, deforested and divided by land grabbers and loggers. In this way, the primitive accumulation underway in the Amazon is structural and not just generic, it seeks to transform everything into commodity, through the productive capacity of capital and its dynamics of the most value.